Analisis Perbandingan Evaluasi Usability Menggunakan Metode Berbasis Pengguna dan Expert pada Aplikasi Mobile Gapura UB - Sabda Norman Hayat; Fatwa Ramdani; Diah Priharsari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Gapura UB is an academic portal mobile application to access academic information and services in the Brawijaya University campus environment. Based on the results of interviews with the developers, stated that the application has never been evaluated usability by testing usability to its users or conducted an inspection by an expert. Even though usability evaluation is an important element that makes it possible to add insight into usability problems in the application. This study aims to identify the usability problem of the application and compare the effectiveness of four evaluation methods used in this study: usability testing, interviews, surveys, and heuristic evaluation. Data is collected from users in the student category and expert evaluator. Details of the number of respondents used are usability testing (N = 10), interviews (N = 10), surveys (N = 110), and heuristic evaluation (N = 3). The four methods together identified a total of 44 usability problems: 45% through heuristic evaluation, 24% through surveys, 17% through interviews and 14% from usability testing, with a few similar findings. These problems are then categorized using Usability Taxonomy Problem (UPT) which divides the problem into 5 categories with details of 17 categories of visualness, 6 categories of language, 3 categories of manipulation, 11 categories of task-mapping and 7 others including the category of task-facilitation. The results of this study prove that the four methods are complementary, each method provides a unique insight to improve the usability of the application user interface. The researcher recommends using a multi-method approach when evaluating application usability because it can provide a more comprehensive representation of usability issues.